Animal Housing and Human-Animal Relations Politics, Practices and Infrastructures - Bjørkdahl, Kristian; Druglitrø, Tone (Routledge Human-Animal Studies Series, 2016)
This book provides an in-depth investigation into the practices of animal housing systems with international contributions from across the humanities and social sciences. By attending to a range of different sites such as the zoo, the laboratory, the farm and the animal shelter, to name a few, the book explores material technologies from the perspective that these are integrated parts of a larger biopolitical infrastructure and questions how animal housing systems, and the physical infrastructures that surround central human-animal practices, come into being. Chapter 11 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781138854116_oaChapter11.pdf